Management of Foreign Exchange Risk - Petrová, Lucie (2018)
The objective of this thesis is to propose effective methods of hedging foreign exchange risk to small and medium-sized companies through advanced strategies of managing foreign exchange risk. The focus is put both on the deployment of the internal and the external hedging strategies. The theoretical part of the thesis is followed by a case study of the Aircraft Industries, the leading manufacturer of small aircraft in the Czech Republic. After a detailed analysis of the company's functioning including its currency exposure assessment and the resulting gains and losses over the period of 2009-2019, applicable recommendations are drawn for the company's future hedging strategy.